The Potential of Bitter Leaf (Vernonia amygdalina) in Herbal Medicine as Anti-Inflammatory Agent - Fawwaz, Muammar; Pratama, Mamat; Latu, Saparuddin; Rahayu, Rita; Nurkamilah, Andi (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractThe inflammatory process involves increased vascular permeability, protein denaturation, and membrane alteration. Flavonoids are a class of secondary metabolites with biological and pharmacological activities, including anti-inflammatory. The bitter leaf, Vernonia amygdalina (VA), are used in various alternative medicine in several countries, including Indonesia. Chemical components in VA leaf are polyphenolic compounds, flavonoids, terpenes, and coumarins. The previous study exhibited that the anti-inflammatory activities of plants are closely related to the levels of polyphenols and flavonoids. Therefore, this study aimed to evaluate the anti-inflammatory activity of VA leaf and determine the total flavonoid-phenolic content of VA leaf ethanolic extract. The extraction method used maceration by ethanol as a solvent. The anti-inflammatory activity was measured by protein denaturation inhibition properties. The total flavonoid and phenolic content were determined by colorimetric and Folin-Ciocalteu methods, in which both procedures were measured by UV-Visible spectrophotometry at maximum wavelength. The results showed that VA leaf ethanolic extract has an anti-inflammatory effect with a half inhibition concentration (IC50) of 346.23 μg/mL. The total flavonoid and phenolic content of the ethanolic extract of VA leaves were 25.62 mgQE/g extracts and 21.47 mgGAE/g extract, respectively. Thus, the ethanolic extract of VA leaves can potentially be developed as an anti-inflammatory agent in herbal medicine.Keywords: anti-inflammatory, flavonoid, gallic acid, phenolic, quercetin AbstrakProses inflamasi melibatkan peningkatan permeabilitas vaskular, denaturasi protein, dan perubahan membran. Flavonoid merupakan senyawa metabolit sekunder dengan aktivitas biologis dan farmakologis potensial, termasuk sebagai antiinflamasi. Daun pahit, Vernonia amygdalina (VA), digunakan dalam berbagai pengobatan alternatif di beberapa negara, termasuk Indonesia. Komponen kimia dalam daun VA adalah senyawa polifenol, flavonoid, terpen, dan kumarin. Studi sebelumnya menunjukkan bahwa aktivitas anti-inflamasi tanaman terkait erat dengan kadar polifenol dan flavonoidnya. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi aktivitas antiinflamasi daun VA dan mengetahui kandungan flavonoid-fenolik total pada ekstrak daun VA. Metode ekstraksi menggunakan maserasi dengan etanol sebagai pelarut. Aktivitas antiinflamasi diukur dengan menggunakan metode penghambatan denaturasi protein. Kandungan total flavonoid dan fenolik ditentukan dengan metode kolorimetri dan Folin-Ciocalteu. Kedua prosedur tersebut diukur pada spektrofotometri UV-Visible pada panjang gelombang maksimum. Hasil penelitian menunjukkan bahwa ekstrak etanol daun VA memiliki efek anti-inflamasi dengan konsentrasi daya hambat 50% (IC50) sebesar 346,23 µg/mL. Kandungan total flavonoid dan fenolik ekstrak etanolik daun VA berturut-turut adalah 25,62 mgQE/g ekstrak dan 21,47 mgGAE/g ekstrak. Dengan demikian, ekstrak etanol daun VA berpotensi untuk dikembangkan sebagai agen anti-inflamasi dalam pengobatan herbal.Kata kunci: anti-inflamasi, asam galat, fenolik, flavonoid, quercetin